Performance Assessment of Open-Loop and Closed-Loop Generation Rate Constraint Models for Optimal LFC of the Three-Area Reheat Thermal System - Sai Kalyan, CH. Naga; Goud, B. Srikanth; Reddy, Ch. Rami; Kumar, M. Kiran; Bajaj, Mohit; El-Naggar, Mohamed F.; Kamel, Salah (Frontiers in Energy Research, 2022)
In this paper, a novel investigation is performed to showcase the best suitable structure of generation rate constraint (GRC) for three area reheat thermal power system (RTPS) in order to obtain load frequency control (LFC) optimally. For investigation purpose, two GRC models which are widely implemented in literature without providing any discussion of their selection and suitability are confiscated in this paper. Two GRC structures deliberated in present paper are termed as open loop and closed loop model. The performance of three area reheat thermal unit is examined with these two GRC structures for a perturbation of 10% step load (10%SLP) on area-1. Investigation is performed under the governing of three-degree-of-freedom PID (3DOFPID) controller fine-tuned using water cycle algorithm (WCA) subjected to index integral square error (ISE) minimization. However, the efficacy of proposed WCA tuned 3DOFPID controller is revealed with other control approaches available in literature up on implementing to widely accepted model of two-area hydro thermal system. Finally, simulation results and sensitivity analysis reveals the suitable GRC structure for three-area reheat thermal unit to obtain LFC optimally with high performance.